Antagonistic Roles of ESCRT and Vps Class C/HOPS Complexes in the Recycling of Yeast Membrane Proteins - Bugnicourt, Amandine (The American Society for Cell Biology, 2004)
In Saccharomyces cerevisiae, deficiencies in the ESCRT machinery trigger the mistargeting of endocytic and biosynthetic ubiquitinated cargoes to the limiting membrane of the vacuole. Surprisingly, impairment of this machinery also leads to the accumulation of various receptors and transporters at the plasma membrane in both yeast and higher eukaryotes. Using the well-characterized yeast endocytic cargo uracil permease (Fur4p), we show here that the apparent stabilization of the permease at the plasma membrane in ESCRT mutants results from an efficient recycling of the protein. Whereas several proteins as well as internalized dyes are known to be recycled in yeast, little is known about the machinery and molecular mechanisms involved. The SNARE protein Snc1p is the only cargo for which the recycling pathway is well characterized. Unlike Snc1p, endocytosed Fur4p did not pass through the Golgi apparatus en route to the plasma membrane. Although ubiquitination of Fur4p is required for its internalization, deubiquitination is not required for its recycling. In an attempt to identify actors in this new recycling pathway, we found an unexpected phenotype associated with loss of function of the Vps class C complex: cells defective for this complex are impaired for recycling of Fur4p, Snc1p, and the lipophilic dye FM4-64. Genetic analyses indicated that these phenotypes were due to the functioning of the Vps class C complex in trafficking both to and from the late endosomal compartment.